Organizational and Methodical Support of Pedagogical Practice of the Future Teachers as for the Implementation of Gender Approach in the Process of Education and Teaching of High School Pupils - Olga Frasiniuk (Pedagogical Discourse, 2012)
The article describes the results of the pedagogical experiment of the problem of organization of the professional training of the future teachers in the aspect of implementation of gender perspective to teaching and education of high school pupils. Particular attention is paid to the reflection of the technology of organizational and methodological support of pedagogical practice for future teachers to master the techniques of „anti-sexizm” and gender measurement of educational area of school.